2023
DOI: 10.54268/baskara.5.2.193-205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of E-Service Quality, Website Quality, Promotion, and E-Trust on Repurchase Intentions at E-Commerce Shopee in DKI Jakarta

Abstract: This study aims to analyze e-Service Quality, Website Quality, Promotion, and e-Trust against Shopee's Repurchase Intention in DKI Jakarta. This study uses a quantitative approach, and because the population in this study cannot be generalized with certainty, the result is that the sample selection uses a non-probability purposive sampling approach. Obtained 200 samples that have been confirmed as feasible for testing, because they have gone through the data screening stage. The first data analysis uses a desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…1 October 2023 has a significant effect on increasing company revenue by utilizing digital marketing such as e-commerce, Facebook and Instagram. As for (Syacroni et al, 2023) and(Ayu Larasati et al, 2022) found that implementing digital marketing strategies can increase sales of company products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 October 2023 has a significant effect on increasing company revenue by utilizing digital marketing such as e-commerce, Facebook and Instagram. As for (Syacroni et al, 2023) and(Ayu Larasati et al, 2022) found that implementing digital marketing strategies can increase sales of company products.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, integrating targeted communications with online services according to the needs of each individual or specific customer. (Syacroni et al, 2023) In short, digital marketing is an activity that achieves marketing goals through the application of technology and digital media, especially the internet. According to (Purwana et al, 2017), Digital marketing is the activity of promoting and finding markets through digital media online using various means such as social networks.…”
Section: Digital Marketingmentioning
confidence: 99%
“…SEM is an analytical technique used to test and estimate causal relationships by integrating path analysis and factor analysis (Hamid & Anwar, 2019). This study uses SEM-PLS analysis because the sample size is small and the data is measured on an ordinal scale (Putri, Meisanti, & Sukrianto, 2023) (Syacroni et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Sari & Wening (2022) also found the results that customer satisfaction has an insignificant and negative effect on customer loyalty. Not to forget, Syachrony et al (2023) in his research found the results that e-service quality and website quality have an insignificant and negative effect on repurchase intention.…”
Section: E-loyaltymentioning
confidence: 96%